Percepção ambiental dos pescadores artesanais da região do Parque Nacional de Ilha Grande PR/MS após a formação do reservatório de Itaipu: conhecimentos tradicionais e a interação homem-natureza - Duarte, Bárbara Machado (2021)
The flooding of the Sete Quedas falls, by the formation of the HPP Itaipu lake in the Paraná River, replaced the natural obstacle that separated two distinct fish provinces, generating impacts on fishing. For the local population located on the stretch above Sete Quedas falls, especially for traditional fishermen, the flooding caused social, cultural and economic losses. Given the above, the aim of this study was to analyze the environmental perception of fishermen in the Ilha Grande National Park region, regarding the changes in fishing in the region after the Itaipu reservoir formation. For data collection, a non-probabilistic sampling design was used, with a qualitative approach, using a questionnaire for the interviews. The results showed that fishermen have knowledge and environmental perception of the changes that have occurred over the past 40 years, since the formation of the Itaipu reservoir, and the consequences of changes in fishing areas and housing, in which they are inserted. Many fishermen have a negative perception about the creation of conservation units and their importance for the conservation of biodiversity. In this sense, it is necessary the action of municipal, state and federal public authorities, supported by scientific information, guiding educational environmental actions, measures to mitigate the environmental impacts generated and support to the fishermen. We also hope that the information generated in this study can contribute to a greater dissemination of scientific knowledge and contribute to improving the life of the community.